Activation of dormant ovarian follicles to generate mature eggs - Li, Jing (National Academy of Sciences, 2010)
Although multiple follicles are present in mammalian ovaries, most of them remain dormant for years or decades. During reproductive life, some follicles are activated for development. Genetically modified mouse models with oocyte-specific deletion of genes in the PTEN-PI3K-Akt-Foxo3 pathway exhibited premature activation of all dormant follicles. Using an inhibitor of the Phosphatase with TENsin homology deleted in chromosome 10 (PTEN) phosphatase and a PI3K activating peptide, we found that short-term treatment of neonatal mouse ovaries increased nuclear exclusion of Foxo3 in primordial oocytes. After transplantation under kidney capsules of ovariectomized hosts, treated follicles developed to the preovulatory stage with mature eggs displaying normal epigenetic changes of imprinted genes. After in vitro fertilization and embryo transfer, healthy progeny with proven fertility were delivered. Human ovarian cortical fragments from cancer patients were also treated with the PTEN inhibitor. After xeno-transplantation to immune-deficient mice for 6 months, primordial follicles developed to the preovulatory stage with oocytes capable of undergoing nuclear maturation. Major differences between male and female mammals are unlimited number of sperm and paucity of mature oocytes. Thus, short-term in vitro activation of dormant ovarian follicles after stimulation of the PI3K-Akt pathway allows the generation of a large supply of mature female germ cells for future treatment of infertile women with a diminishing ovarian reserve and for cancer patients with cryo-preserved ovaries. Generation of a large number of human oocytes also facilitates future derivation of embryonic stem cells for regenerative medicine.